WORKSHOP PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN ABAD 21 DAN PENYUSUNAN LKPD BAGI GURU MATEMATIKA - Erik Santoso; Dedi Nurjamil (Universitas Trisakti, 2020)
Workshop on the development of learning tools based on 21st Century learning models is motivated by the desire of mathematic teachers in the Ciawi Region of Tasikmalaya Regency to innovate in learning. This workshop discussed so that mathematics teachers in the Ciawi Region of Tasikmalaya Regency get a clear understanding of learning tools that are appropriate for the 21st Century. Community service methods use training methods that are held for 3 days, two days face to face and one day of independent assignment. Service starts from the planning of the theme, then begins with the evaluation of the activities. Through the dedication activities that were concluded the workshop participants discussed more about the material of the 21st Century learning tools and then seen from the responses the participants showed positively in the workshop activities of the development of the 21st Century learning tools.